2020
DOI: 10.4018/ijghpc.2020010102
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Multiple Parallel Queuing Model to Enhance QoS in Cloud Computing

Abstract: Among the different QoS metrics and parameters considered in cloud computing are the waiting time of cloud tasks, execution time of tasks in VM's, and the utilization rate of servers. The proposed model was developed to overcome some of the pitfalls in the existing systems among which are sub-optimal markdown in the queue length, waiting time, response time, and server utilization rate. The proposed model contemplates on the enhancement of these metrics using a Hybrid Multiple Parallel Queuing approach with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In [51], the authors suggested a DRL-based service composition model for cloud computing that was also QoS-aware, considering logistics, reliability, cost, and time as the QoS parameters. The authors of [52] took a slightly different approach and recommended improving these metrics using a Hybrid Multiple Parallel Queuing Approach. The arrival rate, service rate, and the number of servers were the QoS parameters in this study.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In [51], the authors suggested a DRL-based service composition model for cloud computing that was also QoS-aware, considering logistics, reliability, cost, and time as the QoS parameters. The authors of [52] took a slightly different approach and recommended improving these metrics using a Hybrid Multiple Parallel Queuing Approach. The arrival rate, service rate, and the number of servers were the QoS parameters in this study.…”
Section: Related Workmentioning
confidence: 99%
“…In the following section, we review the proposed models in relation to the techniques and list most of the QoS parameters that have been used in prior related works. [12], [21], [24], [27], [29], [30], [31], [34], [35], [38], [39], [43], [44], [46], [48], [51], [52] 16%…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…But, it does not consider the traffic flow during migration to solve any conflicts. Afzal & Kavitha (24) developed a hybrid multiple parallel queuing methods for improving the Quality-of-Service (QoS) in cloud computing. But, it assumes the traffic arrival rate and service rate were constant.…”
Section: Literature Surveymentioning
confidence: 99%
“…Different load balancing algorithms have been proposed such as in Afzal & Abdur Rahman (2020) which proposed a load balancing approach that aimed at minimizing the whole task’s executing time and reached a satisfactory result. However, it did not consider the migration time of the task through the network.…”
Section: Introductionmentioning
confidence: 99%